2021
DOI: 10.2196/32351
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Digital Mental Health Intervention in Adults With Cardiovascular Disease Risk Factors: Analysis of Real-World User Data

Abstract: Background The American Heart Association has identified poor mental health as a key barrier to healthy behavior change for those with cardiovascular disease (CVD) risk factors such as high blood pressure, high cholesterol, and diabetes. Digital mental health interventions, like those delivered via the internet to computers or smartphones, may provide a scalable solution to improving the mental and physical health of this population. Happify is one such intervention and has demonstrated evidence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 120 publications
1
6
0
2
Order By: Relevance
“…The purpose of this analysis was to explore whether older adults would engage with a digital well-being intervention and the extent to which engaging with this intervention led to improvements in subjective well-being and anxiety symptoms. Our results show that approximately one-third of older adults who qualified for our analysis engaged with the program at the recommended level, which is consistent with the rates of engagement reported in other analyses of Happify users that did not include older adults [30].…”
Section: Principal Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…The purpose of this analysis was to explore whether older adults would engage with a digital well-being intervention and the extent to which engaging with this intervention led to improvements in subjective well-being and anxiety symptoms. Our results show that approximately one-third of older adults who qualified for our analysis engaged with the program at the recommended level, which is consistent with the rates of engagement reported in other analyses of Happify users that did not include older adults [30].…”
Section: Principal Findingssupporting
confidence: 89%
“…Happify is a self-guided wellness program that aims to improve psychological well-being by delivering brief gamified activities adapted from evidence-based activities from various therapeutic approaches. Previous research has shown that completing 2 or more activities via Happify per week led to significant improvements in subjective well-being and anxiety symptoms after 6 weeks [29][30][31], but none of these studies examined the effects of age or focused specifically on older adults. Therefore, in the current retrospective analysis, we analyzed data from real-world Happify users who self-reported being aged ≥65 years to determine whether completion of intervention activities was related to changes in subjective well-being and anxiety symptoms after at least six weeks of use.…”
Section: Objectivesmentioning
confidence: 99%
“…Universal efforts and tailored, culturally appropriate methods will be needed to direct individuals to resources for improving or maintaining CVH, potentially ameliorating the negative impacts of SDOH and psychological health and promoting positive social and psychological assets. 143,149 Ubiquitous health technology can put important CVH information in the hands of traditionally underserved populations. However, contextual factors (SDOH, access to health care and health technology, health literacy, and psychological health) mediate individuals’ access to health technology and information and can affect their ability to maintain or achieve optimal CVH.…”
Section: Implementation Of Cvh In Clinical Practicementioning
confidence: 99%
“…A variety of strategies have been proposed to collect lifestyle data and house it within the EHR system, 142 including the use of brief questionnaires on computers or tablets in the waiting room or through patient portals before a visit. Some investigators and companies have created standalone apps to collect self-reported lifestyle data, 143,144 although these have the disadvantage of not being integrated within the EHR. As technology continues to evolve, wearable devices may offer the ability to replace self-reported data on PA, BP, and sleep with objectively measured data.…”
Section: Data Sources For Monitoring Cvhmentioning
confidence: 99%
“…In so doing, consideration of the important (aforementioned) foundational contexts of CVH, SDOH, and the psychological well-being of patients from diverse populations is essential with aim of mitigating the nega-tive impacts of SDOH and promoting positive social and psychological assets. [8][9][10] Relatedly, effective communication with patients in diverse settings regarding CVH requires attention to the SDOH with the goal of promoting CVH equity. The LE8 writing group also provides recommendation for promoting CVH in neighborhoods and communities, going beyond traditional settings and considering the sociocultural context of individuals and families.…”
Section: Implementation Of Life's Essential 8 In Clinical Practice An...mentioning
confidence: 99%